Onychomadesis in a 20-Month-Old Child with Kawasaki Disease - Alexander K. C. Leung; Kin Fon Leong; Joseph M. Lam (Hindawi Limited, 2019)
Kawasaki disease is characterized by fever for ≥ five days, bilateral bulbar conjunctival injection without exudate, polymorphous rash changes in the extremities, oral mucosal changes, and cervical lymphadenopathy. We report a 20-month-old boy with Kawasaki disease who had onychomadesis affecting the fingernails and toenails bilaterally. To our knowledge, there were three reported cases of onychomadesis associated with Kawasaki disease, to which we add another one. We suggest keeping in mind the possibility of onychomadesis as a nail sequela of Kawasaki disease.